2018
DOI: 10.1016/j.joen.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Filling Quality of a Premixed Calcium Silicate Endodontic Sealer Applied Using Gutta-percha Cone-mediated Ultrasonic Activation

Abstract: Endoseal MTA performs best when used with GP cone-mediated ultrasonic activation. Furthermore, stereomicroscopic observation of sections of the specimens should be performed when evaluating root canal filling quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 35 publications
1
91
0
2
Order By: Relevance
“…In addition to low solubility, endodontic materials should not have a high percentage of voids (Gandolfi et al 2016), since the presence of voids may increase post-treatment apical periodontitis (Bas ßer Can et al 2017). Hence, the current study also investigated the presence of voids using micro-CT. Micro-CT is a highly accurate, nondestructive tool for measuring voids (Huang et al 2018, Kim et al 2018. A low percentage of voids was detected for the materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to low solubility, endodontic materials should not have a high percentage of voids (Gandolfi et al 2016), since the presence of voids may increase post-treatment apical periodontitis (Bas ßer Can et al 2017). Hence, the current study also investigated the presence of voids using micro-CT. Micro-CT is a highly accurate, nondestructive tool for measuring voids (Huang et al 2018, Kim et al 2018. A low percentage of voids was detected for the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a limitation of the present study was the pixel size of 18 lm applied during micro-CT scanning. Although the image resolution allowed voids to be segmented and quantified, smaller pixel sizes improve image quality and detection of voids (Huang et al 2017, Kim et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being easier to use and requiring less time spent on obturation, according to our previous study, the SC technique may leave several voids in irregularly shaped canals [ 7 ]. These voids are of great concern as they reduce the filling quality and can serve as hubs for microbial housing, leading to reinfection and treatment failure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These voids are of great concern as they reduce the filling quality and can serve as hubs for microbial housing, leading to reinfection and treatment failure [ 8 ]. In this respect, we previously introduced a sophisticated method using an ultrasonic-mediated SC technique to reduce void formation [ 7 ]. We showed that the technique was more beneficial to obturate the root canal with less void formation compared to warm vertical compaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation